2015
DOI: 10.1007/s13277-015-4018-6
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3σ confers cisplatin resistance in esophageal squamous cell carcinoma cells via regulating DNA repair molecules

Abstract: Esophageal squamous cell carcinoma (ESCC) is the predominant type of esophageal cancer in Asia. Cisplatin is commonly used in chemoradiation for unresectable ESCC patients. However, the treatment efficacy is diminished in patients with established cisplatin resistance. To understand the mechanism leading to the development of cisplatin resistance in ESCC, we compared the proteomes from a cisplatin-resistant HKESC-2R cell line with its parental-sensitive counterpart HKESC-2 to identify key molecule involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Recently stromal expression of 14-3-3σ has been demonstrated in endometrial carcinomas and, similar to our results, the neoexpression by fibroblasts in areas of desmoplasia at the IF could be indicative of an active proinvasive environment within the extracellular matrix [40]. To provide more evidence of the role of 14-3-3σ in cancer development, recently it has been shown that 14-3-3σ provides chemoresistance properties to SCC and this fact, along with the anti-apoptotic properties of 14-3-3σ in tumoral cells, highlights the potential of this protein as a very promising biomarker and therapeutic target for penile SCC [18,[41][42][43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently stromal expression of 14-3-3σ has been demonstrated in endometrial carcinomas and, similar to our results, the neoexpression by fibroblasts in areas of desmoplasia at the IF could be indicative of an active proinvasive environment within the extracellular matrix [40]. To provide more evidence of the role of 14-3-3σ in cancer development, recently it has been shown that 14-3-3σ provides chemoresistance properties to SCC and this fact, along with the anti-apoptotic properties of 14-3-3σ in tumoral cells, highlights the potential of this protein as a very promising biomarker and therapeutic target for penile SCC [18,[41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…E-cadherin and vimentin are proteins associated with the epithelial-mesenchymal transition (EMT) process, which have been associated with a poorer prognosis [13,14]. Additionally, 14-3-3σ is an oncoprotein that promotes cell proliferation, survival, invasiveness, metastasis and chemoresistance by binding and modulating various molecular pathways in vulvar, cervical and head and neck SCC [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…[57][58][59][60][61] Many studies have reported that 14-3-3 sigma is closely related to tumor resistance. [62][63][64][65][66] In our preliminary study, SFN was highly expressed in CNE2DDP cells, which is the basis of our follow-up study.…”
Section: Discussionmentioning
confidence: 72%
“…Lee et al[12] reported that the novel oxygen carrier YQ23 enhanced the DDP response of chemoresistant esophageal tumor xenografts, as well as reducing tumor size and the number of animals with invasive tumors. Lai et al[13] provided evidence that 14-3-3σ, or its related DNA repair molecule, is a promising therapeutic target for counteracting DDP resistance in esophageal squamous cell carcinoma. Furthermore, Yu et al[14] suggested autophagy is a novel target to improve the efficiency of DDP in human esophageal cancers with acquired resistance.…”
Section: Discussionmentioning
confidence: 99%